AB0298 A lower waist circumference is associated with clinical remission in patients with established rheumatoid arthritis. (12th June 2018) - Gamboa-Cárdenas, R.V.; Ugarte-Gil, M.F.; Medina, M.; Zevallos, F.; Pimentel-Quiroz, V.; Elera-Fitzcarrald, C.; Reategui-Sokolova, C.; Alfaro-Lozano, J.; Cucho-Venegas, J.M.; Rodriguez-Bellido, Z.; Pastor-Asurza, C.A.; Perich-Campos, R.A.
Abstract : Background: Abdominal Obesity is highly prevalent in patients with RA and this condition is associated with adverse metabolic outcomes, but information about the impact of this condition in clinical activity disease is scarce, specially in our region Objectives: To assess the association between central obesity with baseline clinical activity in a cohort of patients with established rheumatoid arthritis (RA). Methods: Cross-sectional baseline analysis of a single centre RA cohort. This cohort began at 2011 and includes patients with a diagnosis of RA ACR EULAR 2010 criteria), followed by semestral visits. In this analysis, clinical disease activity was measured by SDAI, clinical remission and low disease activity (LDA) was defining according SDAI categories (a value <3.3, and ≤11, respectively), also definition of remission by the ACR-EULAR 2011 was applied (tender and swollen joint counts≤1, CRP ≤1 mg/dl, and PGA≤1 with patient-reported outcomes on a scale of 0–10, or SDAI≤3.3). Patients with chronic pain disease (fibromyalgia, neuropathic pain and neurologic disorders such as neuropathies) and diagnosis of depression were excluded. Waist circumference (WC) was measured as a continue variable (cm). Potential basal confounders associated with activity disease were analysed: socio demographics variables (age at diagnosis, gender, disease duration, delay of DMARDs treatment, education), anticitrullinated antibody peptide (antiCCP), medication (use and dose of corticosteroid, use of cDMARDs and bDMARDS). Continuous variables were expressed as means and SDs, and categorical variables as percentages and 95% confidence intervals (95% CIs). Univariable and multivariable binary logistic regression models were examined in order to determine the association between abdominal perimeter and remission. Results: Four hundred and twenty-five from 596 subjects of the cohort were include. The mean (SD) age was 58.5 (11.8) years. Disease duration was 15.2 (14.0) years; 90.4% were women and 75.8% were anti CCP positive. Two hundred and fifty-one patients (59.1%) have received glucocorticoids, 50.1% at least one DMARD and only 5.4% had received at least one biologic compound. The mean WC was 98.2 (11.3) cm and central obesity prevalence was 87.8% in men and 96.7% in woman. The baseline SDAI was 29.9 (24.1). Remission was met only by 1.7% patients and remission/LDA by 13.2% subjects. In the univariate analysis, a less WC was associated with remission(OR=0.9;CI:0.8–0.9;p=0.042); this association remained significant in the multivariable analysis (OR=0.9;CI:0.8–0.9;p=0.022). Conclusions: A lower waist circumference is associated with clinical remission in patients with established RA. This condition should be taken in account in the baseline measure of activity disease. Disclosure of Interest: None declared